2014
DOI: 10.1177/00333549141296s403
|View full text |Cite
|
Sign up to set email alerts
|

Preparedness and Emergency Response Research Centers: Using a Public Health Systems Approach to Improve All-Hazards Preparedness and Response

Abstract: In 2008, at the request of the Centers for Disease Control and Prevention (CDC), the Institute of Medicine (IOM) prepared a report identifying knowledge gaps in public health systems preparedness and emergency response and recommending near-term priority research areas. In accordance with the Pandemic and All-Hazards Preparedness Act mandating new public health systems research for preparedness and emergency response, CDC provided competitive awards establishing nine Preparedness and Emergency Response Researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
10
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 50 publications
0
10
0
1
Order By: Relevance
“… (1) (Anguelovski et al, ; Brown et al, ); (2) (Kehinde, ); (3) (Lizzaralde, ); (4) (Brown et al, ); (5) (Anguelovski et al, ); (6) (Bornstein et al, ; Brown et al, ); (7) (Lizzaralde, ; Sciulli et al, ; Tadele & Manyena, ); (8) (Bornstein et al, ); (9) (Anguelovski et al, ; Chelleri, Schuetze, et al, ; Chelleri, Waters, et al, ); (10) (Leinhos et al, ; Qari et al, ); (11) (Plough et al, ; Qari et al, ); (12) (Motta et al, ); (13) (Drakaki & Tzionas, ; Plough et al, ); (14) (Plough et al, ); (15) (Roberts, ); (16) (Carthey et al, ); (17) (Siri et al, ); (18) (Carthey et al, ; Plough et al, ). …”
Section: Resultsunclassified
See 1 more Smart Citation
“… (1) (Anguelovski et al, ; Brown et al, ); (2) (Kehinde, ); (3) (Lizzaralde, ); (4) (Brown et al, ); (5) (Anguelovski et al, ); (6) (Bornstein et al, ; Brown et al, ); (7) (Lizzaralde, ; Sciulli et al, ; Tadele & Manyena, ); (8) (Bornstein et al, ); (9) (Anguelovski et al, ; Chelleri, Schuetze, et al, ; Chelleri, Waters, et al, ); (10) (Leinhos et al, ; Qari et al, ); (11) (Plough et al, ; Qari et al, ); (12) (Motta et al, ); (13) (Drakaki & Tzionas, ; Plough et al, ); (14) (Plough et al, ); (15) (Roberts, ); (16) (Carthey et al, ); (17) (Siri et al, ); (18) (Carthey et al, ; Plough et al, ). …”
Section: Resultsunclassified
“…This approach recognizes the need for institutional actors to learn from multiple other actors and continually improve their health and emergency preparedness system designs. Research networks are creating evidence‐based tools for public health preparedness (Leinhos, Qari, & Williams‐Johnson, ).…”
Section: Resultsmentioning
confidence: 99%
“…3,4 Beginning in FY 2008, the Centers for Disease Control and Prevention (CDC) funded nine Preparedness and Emergency Response Research Centers (PERRCs) in accredited schools of public health to conduct research to strengthen public health preparedness systems. 5,6 The conceptual approach to the PERRC program goals and objectives was guided by an Institute of Medicine (IOM) letter report generated at the request of the CDC to define near-term (3-5 years) PHEPR research priorities. 4 The IOM report recommended 4 priority areas for research: 1) enhancing the usefulness of PHEPR training, 2) improving PHEPR communications, 3) creating and maintaining sustainable PHEPR systems, and 4) generating criteria and metrics to measure the efficiency and effectiveness of PHEPR system activities.…”
mentioning
confidence: 99%
“…The ANA defines disaster competencies as "an expected and measurable level of nursing performance that integrates knowledge, skills, abilities, and judgment, based on established scientific knowledge and expectations for nursing practice" (ANA, 2015). The ENA has built on the ANA standards and created the Emergency Nursing: Scope and Standards of Practice document that is specific to demonstrate competence of emergency nursing as a specialty(Harding et al, 2013).The IOM identified knowledge gaps in public health systems preparedness and emergency response and recommended priority research areas(Leinhos, Qari, & Williams-Johnson, 2014). Looking back at the Pandemic and All-Hazards Preparedness Act (PAHPA) of 2006, the IOM identified gaps in knowledge about public health systems preparedness and emergency response that included needs for research, training, preparedness, and criteria for evaluating public health emergency preparedness, response, and recovery, and metrics to measure their effectiveness and efficiency(Leinhos et al).…”
mentioning
confidence: 99%
“…After careful screening of 432 references, information from 68 articles were reviewed in depth. Research demonstrated that although there is an international consensus that nurses are key players in emergency response(Leinhos et al, 2014), demographically, countries vary in perceptions of nursing qualifications for disaster response. The literature examined in this study identified the need for nurses to not only prepare for, but train for disaster response.…”
mentioning
confidence: 99%